Outcome of AO Type C Fractures Distal Radius treated with Volar Locking Plates in a Tertiary care center Lahore (Journal of Pakistan Orthopaedic Association, 2020)
Objective: To determine the clinical and radiological outcome of AO Type C fracture distal radius treated with 2.4mm Titanium volar locking plates.Methods: This descriptive study was conducted in Department of Hand and Upper limb Surgery(HULS) Combined Military Hospital(CMH) Lahore Pakistan from 23rd January 2016 to 4th January 2019.All adults patients of either gender with distal radius fractures(Type C) fulfilling the inclusion criteria were treated with 2.4mm volar locking plates. Post operative flexion and extension of the wrist was measured with goniometer and grip strength with a weighing scale. Radiological outcome was determined by comparing pre operative and post operative radial height, radial inclination and volar tilt. P value was calculated for net improvement of radiological outcome and < 0.05 was considered significant.Results: The total number of patients in our study were 52.Mean age of the patients were 40.26 ± 12.7 years(range 18 to 69 years).Male patients were 39(75%) and female 13(25%).Right radius was fractured in 28(53.8%) patients and left in 24(46.1%).AO type C2 fracture was noted in 24(46.1%),C1 in 19(36.5%) and C3 in 9(17.3%) patients. Post operative mean wrist flexion was 78°±7 (range 62° to 80°) and extension 68°±4 (range 60° to 75°)at last follow up. The grip strength was excellent in 22(42.3%), good in 18(34.6%) and average in 12(23%).The mean value of pre operative Radial Height(RH) was improved from5.35±3.32 to 11.42±0.800, Radial Inclination(RI) from 13.83±3.71 to 21.09±0.793 degrees, and Volar Tilt(VT) from 5.43±11.9 to11.22±0.951 degrees. The net improvement in RH, RI and VT was 6.11 ± 2.77, 7.26 ± 2.89 and 15.65 ± 14.26 (P > 0.05).No major complication was documented in our study.Conclusion: Titanium volar locking plates produced excellent functional and radiological outcome in patients with intra articular fractures of the distal radius. We therefore, recommend 2.4mm Titanium volar locking plate as implant of choice to treat Type C fractures.